De novo myeloid sarcoma mimicking gynecological tumors: a retrospective case series of eight patients - Yu Gu; Haoran Zheng; Shengwei Mo; Tao Guo; Lihua Chen; Junjun Yang; Yang Xiang (BMC, 2023)
Abstract Objective To describe myeloid sarcoma (MS) that mimic gynecological tumors and provide guidelines for improving the diagnosis and treatment of patients. Methods This case series study retrospectively analyzed the clinicopathological characteristics and oncological outcomes of female patients who were histologically diagnosed with MS after initially presenting with reproductive-system tumors at the Peking Union Medical College Hospital between January 2000 and March 2022. Results There were eight cases in which MS mimicked cervical cancer, ovarian cancer, or hysteromyoma. Six patients had isolated MS, and the other two had acute myeloid leukemia (AML)-M2. The average age was 39.00 ± 14.26. They each sought advice from a gynecological oncologist at the initial visit, complaining of irregular bleeding (3/8), low abdominal pain (3/8), dysmenorrhea (1/8), or an accidentally found mass (1/8). CT/MRI exams revealed that the average tumor size reached 5.65 ± 2.35 cm, with 50% of the tumors being larger than 8 cm. The final diagnoses were confirmed by biopsy (2/8) or postoperative pathology (6/8); the most frequent positive immunohistochemical markers were Ki-67 (60-90%), MPO (100%), LCA (62.5%), CD43 (62.5%), CD117 (62.5%), CD99 (50%), vimentin (37.5%), and lysozyme (25%). MLL/AF9 gene fusions and CEBPA, JAK2, NRAS, and FLT3-TKD mutations were found in the patients. Six (75%) of the patients showed a complete response after upfront treatment using chemotherapy + surgery and experienced no recurrence during follow-up. The overall survival (OS) rate was 72.9%, and the 5-year OS rate was 72.9% (95%CI: 0.4056-1.000). The median OS was 26 months (range: 3-82). Conclusion For patients with isolated MS, treatment by chemotherapy and surgery are radical procedure, and initial treatment using chemotherapy alone should be considered for MS with synchronous intramedullary AML. Poor response to chemotherapy, short interval to leukemia occurrence, and heavy tumor burden (> 10 cm) could indicate a poor prognosis for patients with MS.